THE CONVERSION OF LPG GAS TO NATURAL GAS: STUDY ABOUT GOVERNMENT POLICY OF NATURAL GAS CONVERSION IN INDONESIA - Hadi Prabowo; Triyuni Sumartono; Bambang Saputra (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
This paper is a literature study and field research to the theme that was raised, the conversion of LPG gas to natural gas: a study about government’s policy of the conversion Indonesia's natural gas. There are three questions in this paper: first, how is the concept of government policy towards the conversion of Indonesia's natural gas? Second, how is the impact of government policies on natural gas conservation in Indonesia? Third, how is the implementation of government policy? By using the concept of analysis to explain the first question, it's about how the concept of government policy towards the conversion of natural gas in Indonesia. The second question is how the impact of government policies on natural gas conversion in Indonesia. And the field approach to explain the third questions, how is the implementation of government policies towards the conversion of natural gas in Indonesia. The results of this paper itself are, first knowing the concept of government policy on natural gas conversion in Indonesia, knowing the impact of government policy on natural gas conversion in Indonesia. Third, is to know the implementation of government policies of natural gas conversion in Indonesia. Keywords. Conversion, LPG Gas, Natural gas, Government Policy